Some Additional Estimates of the Liquidity Preference Function for the United States - Scott, Robert Haney (Journal of Financial and Quantitative Analysis, 1967)
In this paper the results of some new structural estimates of liquidity preference may be found. The justification for presenting them is that they differ from earlier estimates in certain ways. In some cases, the implications of these estimates differ sharply from the implications drawn by other observers on the basis of their estimates.